Spatial characteristics of spontaneous and stimulus-induced individual functional connectivity networks in severe disorders of consciousness - Sitaram, Ranganatha; Yu, Tao; Halsband, Ulrike; Vogel, Dominik; Müller, Friedemann; Lang, Simone; Birbaumer, Niels; Kotchoubey, Boris (Brain and cognition, 2019)
Background - Functional connectivity (fcMRI) analyses of resting state functional magnetic resonance imaging (fMRI) data revealed substantial differences between states of consciousness. The underlying cause-effect linkage, however, remains unknown to the present day. The aim of this study was to examine the relationship between fcMRI measures and Disorders of Consciousness (DOC) in resting state and under adequate stimulation. - Methods and findings - fMRI data from thirteen patients with unresponsive wakefulness syndrome, eight patients in minimally conscious state, and eleven healthy controls were acquired in rest and during the application of nociceptive and emotional acoustic stimuli. We compared spatial characteristics and anatomical topography of seed-based fcMRI networks on group and individual levels. The anatomical topography of fcMRI networks of patients was altered in all three conditions as compared with healthy controls. Spread and distribution of individual fcMRI networks, however, differed significantly between patients and healthy controls in stimulation conditions only. The exploration of individual metric values identified two patients whose spatial metrics did not deviate from metric distributions of healthy controls in a statistically meaningful manner. - Conclusions - These findings suggest that the disturbance of consciousness in DOC is related to deficits in global topographical network organization rather than a principal inability to establish long-distance connections. In addition, the results question the claim that task-free measurements are particularly valuable as a tool for individual diagnostics in severe neurological disorders. Further studies comparing connectivity indices with outcome of DOC patients are needed to determine the clinical relevance of spatial metrics and stimulation paradigms for individual diagnosis, prognosis and treatment in DOC.
Available online: 27 November 2018
Gesehen am 14.10.2019